Preconception Low-Dose Aspirin and Pregnancy Outcomes. Issue 3 (September 2015) - Schisterman, E.F.; Silver, R.M.; Lesher, L.L.; Faraggi, D.; Wactawski-Wende, J.; Townsend, J.M.; Lynch, A.M.; Perkins, N.J.; Mumford, S.L.; Galai, N.
<x xml:space="preserve">Abstract</x> (Lancet. 2014;384(9937):29–36)